2011
DOI: 10.1016/j.jss.2010.11.131
|View full text |Cite
|
Sign up to set email alerts
|

Cross-transfusion of Postshock Mesenteric Lymph Provokes Acute Lung Injury

Abstract: Objective-Substantial investigation has implicated mesenteric lymph as the mechanistic link between gut ischemia/reperfusion (I/R) and distant organ injury. Specifically, lymph diversion prevents acute lung injury (ALI) in vitro and bioactive lipids and proteins isolated from postshock mesenteric lymph (PSML), maintain bioactivity in vitro. However, Koch's postulates remain to be satisfied via direct cross-transfusion into a naïve animal. We therefore hypothesized that real time cross-transfusion of postshock … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…This is demonstrated by prevention of neutrophil priming and accumulation in pulmonary tissues; reduced lung permeability, and histological improvement in lung injury . Furthermore, gut lymph is directly toxic to pulmonary microvascular endothelial cells, and lung injury can be reproduced when donor lymph from a rat subjected to haemorrhagic shock is infused into a naive rat . Clinically, these findings are supported by three non‐randomized studies in AP assessing pulmonary function, one of which observed that arterial oxygenation improved immediately once drainage was instituted …”
Section: Persistent Organ Failurementioning
confidence: 89%
“…This is demonstrated by prevention of neutrophil priming and accumulation in pulmonary tissues; reduced lung permeability, and histological improvement in lung injury . Furthermore, gut lymph is directly toxic to pulmonary microvascular endothelial cells, and lung injury can be reproduced when donor lymph from a rat subjected to haemorrhagic shock is infused into a naive rat . Clinically, these findings are supported by three non‐randomized studies in AP assessing pulmonary function, one of which observed that arterial oxygenation improved immediately once drainage was instituted …”
Section: Persistent Organ Failurementioning
confidence: 89%
“…The “gut-lymph” pathway is therefore important in distant organ injury. However, the factors causing injury remain unknown [6]. Possible factors include Toll-like receptor 4 (TLR4), high-mobility group box 1 protein (HMGB1), endotoxin, as well as bioactive non-microorganism derived proteins and lipoproteins.…”
Section: Introductionmentioning
confidence: 99%
“…2 It has been also demonstrated that mesenteric lymph (ML) plays an essential role in the delivery of cytokines, coagulation factors, cellular breakdown products, and inflammatory lipid mediators into the circulation from the ischemic gut after HS. 3,4 Inflammatory lipid mediators in the ML are thought to play a significant role in the pathogenesis of MOD after HS, and phospholipase A 2 (PLA 2 ) is related to the generation of these mediators. 5 Free fatty acids generated by PLA 2 have been reported to increase the toxicity of ML in an intestinal ischemia/ reperfusion (I/R) model.…”
mentioning
confidence: 99%